Utility of the Age Shock Index in 27312 patients with an acute coronary syndrome. (3rd October 2022) - Rocha Carvalho, P; Monteiro, J; Carvalho, C; Mateus, P; Goncalves, F; Fontes, P; Moreira, J I
Abstract: Introduction: The Shock Index (SI), defined as the ratio of heart rate (HR) to systolic blood pressure (SBP), represents a bedside reflection of the integrated response from the cardiovascular and autonomic systems and has been reported to predict adverse prognosis in patients with acute coronary syndromes (ACS). Age Shock Index (ASI), the product of SI multiplied with age, could also be useful in this setting, but its prognostic value is yet to be determined in ACS patients. Methods: Acute myocardial infarction patients included in a national registry between October 2010 and January 2022. Optimal shock index cutoff was determined according to ROC curve analysis. Patients were categorized into two groups based on their initial ASI. Baseline characteristics, management and outcomes were compared between the two groups. The primary outcome was in-hospital cardiovascular death. Results: A total of 27312 patients were included with a mean age of 66±13 years, 72.3% male, 47.5% with ST-elevation myocardial infarction. Based on ROC analysis, which showed AUC=0.80, the optimal ASI cutoff was 44 (with a sensitivity of 73% and a specificity of 74%); 19997 patients (73.2%) had an ASI <44 and 26.8% had an ASI ≥44. The former group was older (mean age of 75±10.0 vs 63±13.0 years, p<0.001), and had more comorbidities: arterial hypertension (77.3% vs 66.3%, p<0.001), diabetes mellitus (39.8% vs 28.1%, p<0.001), peripheral artery disease (7.1% vs 4.4%, p<0.001) and previous history of heart failure (11.0% vs 4.3%, p<0.001). Patients with ASI ≥44 had higher Killip class at admission and worse left ventricular ejection fraction on discharge (46.0±13.0 vs 53.0±11.0, p<0.001). In a multivariate regression analysis, after adjusting for possible confounders, ASI ≥44 was an independent predictor of cardiovascular death (HR 3.09, 95% CI: 2.56–3.71, p<0.001). ASI was a significantly better predictor of cardiovascular death than Shock Index (AUCASI = 0, 80 vs AUCSI = 0.72, p<0, 0001), but not in comparison to GRACE score (AUCASI=0.80 vs AUCGRACE=0.85, p<0.001) and TIMI (score AUCASI=0.80 vs AUCGRACE=0.84, p<0.001). At one year, using a Kaplan Meyer survival analysis, mortality was higher in patients with ASI ≥44 (log rank p<0.001) Conclusion: ASI can identify almost immediately ACS patients at high risk of cardiovascular death, and combined with its simple use, makes it a practical tool for early risk stratification in these patients. Funding Acknowledgement: Type of funding sources: None.